Compression behaviours of aluminium alloy I-column at low temperatures. (October 2022) - Yan, Jia-Bao; Kong, Guobin; Wang, Zhongxing; Zhang, Lingxin; Wang, Xuan
Abstract: Aluminium alloys have been used in cold-region engineering constructions. To make more comprehensive understandings of aluminium material properties and structural behaviours at cold-region low temperatures ( T ), mechanical properties of aluminium alloy 6061-T6 at different T of −80 – 20 °C were investigated through tensile coupon tests. Then, seven aluminium alloy 6061-T6 I-columns were tested under axial compression and different T of 20, −30, −60, and −80 °C. The failure modes, load-shortening/strain behaviours of aluminium I-columns under low-temperature compression were detailed studied. These tests showed that the decreasing T increased the yield/ultimate strength of aluminium alloy 6061-T6 by 10%, and also increased the axial ultimate compression resistance ( P u ) of I-column by 7% without reductions in their ductility. Finite element models (FEMs) were also developed by ABAQUS for simulating structural behaviours of aluminium I-columns using the obtained low-temperature material properties. Validations of FEM simulations showed its reasonable simulations on compression behaviours of aluminium I-columns. The code equations in Chinese code GB 50429 and Eurocode 9 were also checked to estimate P u of aluminium I-columns at low temperatures. It shows that both codes provided conservative predictions on P u of aluminium I-columns at low temperatures.